Модель бестарифної системи оплати праці в аналізі організації заробітної плати на підприємствах - Погорєлов, Микола Іванович; Миргород, Ганна Вадимівна (НТУ "ХПІ", 2018)
Реформування економіки вимагає створення і забезпечення дієвих ринкових механізмів заробітної плати. Для підприємств найбільш перспективною є модель безтарифної системи оплати праці. Визначення коефіцієнта кваліфікаційного рівня працівника - найбільш відповідальний момент при введенні безтарифної моделі. Розглянено чотири найбільш великих етапи розробки і впровадження безтарифної оплати праці на підприємстві. Запропоновано застосування цієї форми оплати праці як альтернативи застарілим моделям організації заробітної плати у комерційних структурах.

Economy reforms require creation and implementation of effective market mechanisms for remuneration. The disadvantages of existing approaches to the organization of salaries and wages have been detected. The most promising model for enterprises is the non-tariff system of labor compensation. The determination of an employee's qualification level index is the most crucial moment when introducing the non-tariff model. Four most important stages of development and implementation of the non-tariff remuneration of labour at the enterprise are introduced: the issuance of an order as for the preparation to the transition to the new model of remuneration, elaboration of the standard regulations of the non-tariff model of salaries and wages, edition of an order as for the final transition to the new model of salaries and wages, and the аnalysis of the effectiveness of the new remuneration management. This form of remuneration of labour has been suggested for use as an alternative to outdated models of remuneration systems in commercial structures.
The model of the non-tariff system of labor compensation within the analysis of the remuneration management at the enterprise
Keywords: преміювання; коефіцієнт кваліфікаційного рівня; працівник; фінансове становище; конкурентоспроможність; bonuses; qualification level index